Karate Game: Using a Playful and Participatory Approach to Enhancing Children's Social and Motor Perception during the Developmental Age - Giuseppe Giardullo; Sara Aliberti; Italo Sannicandro; Simona Fattore; Rosario Ceruso (OVS LLC, 2024)
Objectives. The study aimed to evaluate the effects of sport-specific educational proposals in school-age sports, currently used in planning of sports activities, such as game-based karate training, on social interactions and improving perceptions of one's motor skills. Materials and methods. The sample consisted of 34 children from the Comprehensive Institute "Matilde Serao" in Ortona, Chieti, attending the third classes of the Primary School, in the school year 2023/2024. The method used was based on the Karate Sport Game protocols in conjunction with the dissemination of the ethical principles inherent to the martial arts. A questionnaire was developed for the purpose of assessing the learners' levels of satisfaction, as well as the perceptions they had about themselves and in relation to others during this training intervention. Results. In the post-implementation evaluation of the educational proposals' results, it was shown that 94.1% of participants had a positive experience engaging in the Game-Karate activities, 82.3% reported feeling significantly supported by the Instructors during the project, and 94.1% were very satisfied with the activities. The application of the Chi-Square test revealed two significant relationships with respect to the concept of opportunity for interaction with all peers. The first pertained to the participants' overall satisfaction with the karate instructional project (p=0.006), while the second concerned the concept of improving teamwork (p=0.006). Conclusion. The findings indicate that Karate Game had a beneficial impact on the participants' emotional sphere, involvement, perceived improvement in motor skills, and group dynamics. In addition, the significant relationships found underscore the importance of social interaction and collaboration in the context of physical activity. These results suggest that playful and participatory approach to the training process in Karate classes can be a valuable resource for the comprehensive development of children's personality and motor skills during the developmental age.